Pengaruh Harga dan Kepercayaan Terhadap Kepuasan Konsumen Pada Jasa Pengiriman J&T Express Kota Kediri - Gunawan Nuryatanto; Indah Yuni Astuti; Rike Kusuma Wardani (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
This study aims to determine the effect of price and trust on consumer satisfaction in J&T Express delivery services in Kediri City. This type of research is quantitative research. The data for this study were obtained through primary and secondary data. The population in this study were consumers of J&T Express in Kediri City. The sample in this study was 100 consumers with the sampling technique using accidental sampling. The analysis techniques used were validity testing, reliability testing, classical assumption testing, multiple linear regression analysis and hypothesis testing. The results of the study showed that the partial t-test results of the price and trust variables influenced consumer satisfaction. The results of the simultaneous F-test showed that price and trust influenced consumer satisfaction.